(untitled) (IITM Journal of Business Studies, 2025)
This paper aims to examine the current behavior qua retail investors regarding India’s non-financial reporting and how non-financial reporting has impacted their decisions. The study further delves into the influence of various factors viz-a-viz non-financial reporting and the investment decision. Non financial reporting has been represented by the standardized Business Responsibility and Sustainability Report. During the investigation and preparation of the present paper, the author has taken three independent variables and one dependent variable. The independent variables taken by the author are environmental variables, social variables, and governance as the third variable, whereas the responding variable is the investment decision. The author tries to collect data by distributing questionnaires among the retail investors who have applied for securities for less than Rs. 2,00,000/- with a sample size of 500 respondents.